Improving Tensile Bond Strength of Orthodontic Bracket by Applying Papain Gel as an Email Deproteinization Agent - Rosyida, Niswati F.; Suparwitri, Sri; Pudyani, Pinandi S. (UI Scholars Hub, 2017)
An effort to improve the bonding between bracket and tooth surface is required. Objective: The aim of this study was to evaluate the effect of papain gel on tensile bond strength (TBS) and adhesive remnant index (ARI) of the orthodontic brackets. Methods: A total of 42 healthy human premolars were randomly divided into six groups. 1) Resin-modified glass ionomer cement (RMGIC) without papain, 2) RMGIC with papain 8%, 3) RMGIC with papain 10%, 4) Composite resin (CR) without papain, 5) CR with papain 8%, 6) CR with papain 10%. The TBS was determined using a universal testing machine. Bond failure was classified according to the ARI. The TBS data were analyzed with Kruskal-Wallis test followed by Mean Whitney tests with 5% of significance level. Results: The mean of TBS(MPa) values of RMGIC groups are without papain (5.03 ± 1.52), papain 8% (4.79 ± 2.61), papain 10% (7.75 ± 1, 48). CR groups without papain (5.45 ± 1.23), papain 8% (2.30 ± 0.73), and papain 10% (4.84 ± 1.72). Bond failure was mainly classified as score 1. The TBS values were statistically influenced by the application of papain and adhesive. Conclusion: The application of papain 10% before RMGIC cementation improves the tensile bond strength and could decrease the bond failure of the orthodontic bracket.